ESTIMATION OF NUTRITIVE VALUE OF “NANNARI KANJI” AND EVALUATION OF ITS ANTI-BACTERIAL ACTIVITY AGAINST STAPHYLOCOCCUS AUREUS, A RESPIRATORY PATHOGEN BY IN VITRO METHOD - SOWMYA S; SUDHA REVATHY S; MEENAKUMARI R (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: To estimate the nutritive value of Nannari Kanji. To evaluate the beneficial effect of Nannari Kanji against the respiratory pathogen, Staphylococcus aureus. To analyze the minerals present in Nannari Kanji. Methods: Nannari Kanji is a polyherbal formulation prepared using Nannari, Karunguruvai rice, and coconut milk by simple boiling method. In the present study, the Nutritive value of Nannari Kanji was analyzed and its antimicrobial activity was studied in terms of minimum inhibitory concentration against the respiratory pathogen, S. aureus. In addition to that mineral analysis was performed using the ICP-OES instrument. Results: In the nutritive analysis, protein (26.83%) was present in large amounts. The antimicrobial activity showed an inhibitory effect against S. aureus at the concentration of 527.02 μg/mL. The mineral analysis confirms the presence of magnesium, iron, and zinc of which magnesium shows a higher value (192.06 ppm). Discussion and Conclusion: Nannari Kanji has potent antimicrobial activity against S. aureus. It has more protein and fat content, which is useful in suppressing respiratory infections. Nannari Kanji contains good magnesium content which is considered to be a good antimicrobial agent.